Language Politeness Education through Language Behaviour Habits: Concerning the Indonesian and Japanese Viewpoints - Ely Triasih Rahayu; Slamet Riyadi; Hartati Hartati; Anggita Stovia; Nisa Roiyasa; Weksa Fradita Asriyama (STAI Hubbulwathan Duri, 2023)
Language politeness has universal characteristics. It means that speech communities from any country have their own language politeness based on the applicable norms. Language politeness education starts from family. Meanwhile, outside family communities, such as schools or society, language politeness education is greatly needed to create positive interactions between language users and certain communities. This research discussed language politeness education in two languages (Indonesian and Japanese) using a comparative qualitative case study in library research. The results of the study informed that Indonesian and Japanese are two languages that implement language politeness through both verbal and non-verbal languages. Verbal language is shown by the chosen polite words, while non-verbal language is shown by the speaking body gestures.